Targeting the melanoma-associated antigen CSPG4 with HLA-C*07:01-restricted T-cell receptors - Kropp, Korbinian N.; Fatho, Martina; Huduti, Enes; Faust, Marilena; Lübcke, Silke; Lennerz, Volker; Paschen, Annette; Theobald, Matthias; Wölfel, Thomas; Wölfel, Catherine (Frontiers in Immunology, 2023)
Chondroitin sulfate proteoglycan 4 (CSPG4), also known as high molecular weightmelanoma associated antigen, is expressed in melanoma but also other tumor entities and constitutes an attractive target for immunotherapeutic approaches. While recent preclinical reports focused on anti-CSPG4 chimeric antigen receptors (CAR), we here explore T-cell receptor (TCR)-based approaches targeting CSPG4. The TCRs of two CSPG4-reactive T-cell clones (11C/73 and 2C/165) restricted by the highly prevalent HLA-C*07:01 allele were isolated and the respective αβTCR pairs were retrovirally expressed in CRISPR/Cas9-edited TCR-knockout T cells for functional testing. We also combined alpha and beta TCR chains derived from 11C/73 and 2C/165 in a cross-over fashion to assess for hemichain dominance. CSPG4 + melanoma, glioblastoma and lung cancer cell lines were identified and, if negative, retrovirally transduced with HLA-C*07:01. Functional tests confirmed specific recognition of CSPG4 + HLA-C*07:01 + target cells by the αβTCR retrieved from the parental T-cell clones and in part also by the cross-over TCR construct 2Cα-11Cβ. Despite high surface expression, the 11Cα-2Cβ combination, however, was not functional. Collectively, 11C/73-and 2C/165-expressing T cells specifically and efficiently recognized CSPG4 + HLA-C*07:01 + cancer cells which warrants further preclinical and clinical evaluation of these TCRs.